Assessing the safety and pharmacokinetics of the monoclonal antibodies, VRC07-523LS and PGT121 in HIV negative women in South Africa: study protocol for the CAPRISA 012A randomised controlled phase I trial. Issue 7 (3rd July 2019) - Mahomed, Sharana; Garrett, Nigel; Capparelli, Edmund; Baxter, Cheryl; Zuma, Nonhlanhla Yende; Gengiah, Tanuja; Archary, Derseree; Moore, Penny; Samsunder, Natasha; Barouch, Dan H; Mascola, John; Ledgerwood, Julie; et al.
Abstract : Introduction: Despite extensive prevention campaigns and scale-up of antiretroviral therapy, HIV incidence among young women in southern Africa remains high. While the development of an efficacious vaccine remains a challenge, the discovery of broadly neutralising monoclonal antibodies (mAbs) has created the opportunity to explore passive immunisation as a long-acting injectable HIV prevention strategy. The purpose of this trial is to provide safety, pharmacokinetic (PK) and functional activity data of VRC07-523LS and PGT121 when administered subcutaneously (SC) to young South African women. Going forward, the aim is to select the ideal dose and/or monoclonal antibody for co-formulation and testing with CAP256-VRC26.25LS, a potent monoclonal antibody against subtype C virus, in an efficacy trial. Methods and analysis: CAPRISA 012A is a randomised, double blinded, placebo-controlled phase I trial to assess the safety and PK profile of two mAbs, VRC07-523LS and PGT121 administered SC to 35 young HIV negative women at low risk for HIV infection. Women will be randomised into seven groups of five participants each. In each group, women will be randomised (4:1) to the active intervention, VRC07-523LS and/or PGT121, or placebo. Participants will be followed up for 24 weeks after the administration of the last dose of study product with a total study duration of 72 weeks. Safety in the study will be assessed by the number and percentage of reactogenicity and adverse events experienced by participants and the relatedness to study product. The PK study design was based on preliminary PK data for VRC07-523LS and PGT121. Ethics and dissemination: Ethical approval has been granted by the South African Health Products Regulatory Authority and by the University of KwaZulu-Natal Biomedical Research Ethics Committee. Results will be presented at international conferences and published in academic peer-reviewed journals. Trial results will be uploaded on the clinical trial registry. Trial registration number: PACTR201808919297244; Pre-results.